2012
DOI: 10.1016/j.cmet.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Links Inflammasomes to Atherosclerotic Progression

Abstract: SUMMARY We investigated the role of autophagy in atherosclerosis. During plaque formation in mice, autophagic markers co-localized predominantly with macrophages (mϕ). Atherosclerotic aortas had elevated levels of p62, suggesting that dysfunctional autophagy is characteristic of plaques. To determine if autophagy directly influences atherogenesis, we characterized Beclin-1 heterozygous-null and mϕ-specific ATG5-null (ATG5-mϕKO) mice, commonly used models of autophagy haploinsufficiency and deficiency, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
487
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(531 citation statements)
references
References 64 publications
24
487
0
5
Order By: Relevance
“…Previous papers show that lipids such as fatty acids or cholesterol are efficient activators of the inflammasome complex. 6,10,52 While the detailed molecular mechanism of lipid-induced inflammasome activation remains to be investigated, mitochondrial dysfunction induced by fatty acids in combination with LPS likely plays an important role in inflammasome activation, which was exemplified by the markedly decreased NAD C :NADH ratio and increased mitochondrial ROS content, consistent with previous papers. 12,24 An in vivo source of TLR (toll-like receptor) ligands which are essential for efficient stimulation of inflammasome in addition to lipid, could be a low-level endotoxin owing to altered intestinal barrier function 53,54 or AHSG (a-2-HS-glycoprotein) that can activate TLR in complex with lipids.…”
Section: Discussionsupporting
confidence: 74%
“…Previous papers show that lipids such as fatty acids or cholesterol are efficient activators of the inflammasome complex. 6,10,52 While the detailed molecular mechanism of lipid-induced inflammasome activation remains to be investigated, mitochondrial dysfunction induced by fatty acids in combination with LPS likely plays an important role in inflammasome activation, which was exemplified by the markedly decreased NAD C :NADH ratio and increased mitochondrial ROS content, consistent with previous papers. 12,24 An in vivo source of TLR (toll-like receptor) ligands which are essential for efficient stimulation of inflammasome in addition to lipid, could be a low-level endotoxin owing to altered intestinal barrier function 53,54 or AHSG (a-2-HS-glycoprotein) that can activate TLR in complex with lipids.…”
Section: Discussionsupporting
confidence: 74%
“…While evidence is limited for the case of the endothelium, in other cell types it appears that autophagy may play a critical role in maintaining overall lipid homeostasis. For instance, mice bearing ATG5-deficient macrophages appear to exhibit increased plaque formation when bred with pro-atherogenic mouse strains (Liao et al, 2012;Razani et al, 2012). While the basis for this increased plaque burden is undoubtedly complex, evidence suggests that macrophage-specific ATG5 deletion results in impaired lipophagy (Sergin & Razani, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Liao et al [1] noted that autophagy prevented lesional macrophage apoptosis and defective efferocytosis and that autophagy deficiency enhanced the total necrotic area in advanced atherosclerotic plaques and the damage caused by oxidative stress in experiments using ldl -/-mice. Razani et [3] provided evidence that autophagy became dysfunctional in AS and that autophagy deficiency, to some extent, led to inflammasome hyperactivation, which further promoted AS progression. The authors of these two articles used LC3/Atg8, p62/SQSTM1 and the double-membrane autophagosomes as autophagy markers.…”
Section: Effects Of Macrophage Autophagy On Apoptosis Inflammation Amentioning
confidence: 99%
“…Furthermore, there is evidence that IP 3 R-mediated Ca 2+ signaling is an indispensable part of the mTORC1-regulated pathway. Although an autophagy-inhibiting role for intracellular Ca 2+ has been reported [22] , it has been demonstrated that under starvation conditions or exposure to rapamycin, an mTORC1 inhibitor, the endoplasmic reticulum (ER) accumulates large amount of Ca 2+ and promotes the release of Ca 2+ through IP 3 Rs, which consequently results in the induction of autophagy [23] .…”
Section: Autophagy and Its Major Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation